Osteophyte compression mimicking a pharyngeal pouch! - Krishnan, Ragitha B.; Krishnan, Binu (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Dysphagia is a broad term encompassing various symptoms due to any condition affecting the normal mechanism of swallowing. The symptoms are often varied like inability to swallow solids and/or liquids, cough on taking liquids, recurrent episodes of aspiration pneumonia and so on. Zenker‘s diverticulum is a not so common condition in which the patient usually presents with hallitosis, delayed regurgitation of feeds in an unchanged manner and foreign body sensation in the throat. Another rare condition is an osteophyte indenting onto the esophagus and causing dysphagia. A 63 year old male presented to the laryngology out patient department with symptoms of food sticking in his throat and regurgitation of feeds in unchanged form which occurred hours after the initial meal. As clinical evaluation and flexible endoscopic evaluation of swallowing were unremarkable he was subjected to a fluoroscopy. Fluoroscopy showed prominent osteophytes at fourth cervical vertebra (C4) and seventh cervical vertebra (C7); the higher one obliterating the apex of right pyriform fossa thereby leading to occasional stagnation of barium in the right pyriform fossa which mimicked a pouch. A computed tomography confirmed the finding of an osteophyte compressing on the lower end of the hypopharynx and giving rise to symptoms similar to that of a pharyngeal pouch. He consequently underwent an osteophyte excision via anterior cervical approach following which he was relieved of his symptoms.